L-Amino Acid Oxidases From Mushrooms Show Antibacterial Activity Against the Phytopathogen Ralstonia solanacearum - Sabotič, Jerica; Brzin, Jože; Erjavec, Jana; Dreo, Tanja; Tušek Žnidarič, Magda; Ravnikar, Maja; Kos, Janko (Frontiers in Microbiology, 2020)
Ralstonia solanaceraum is the quarantine plant pathogenic bacterium that causes bacterial wilt in over 200 host plants, which include economically important crops such as potato, tomato, tobacco, banana and ginger. Alternative biological methods of disease control that can be used in integrated pest management are extensively studied. In search of new proteins with antibacterial activity against R. solanacearum, we identified L-amino acid oxidases (LAOs) from fruiting bodies of Amanita phalloides (ApLAO) and Infundibulicybe geotropa (CgLAO). We describe an optimized isolation procedure for their biochemical characterization, and show that they are dimeric proteins with estimated monomer molecular masses of 72 kDa and 66 kDa, respectively, with isoelectric point of pH 6.5. They have broad substrate specificities for hydrophobic and charged amino acids, with highest Km for L-Leu, and broad pH optima at pH 5 and pH 6, respectively. An enzyme with similar properties is also characterized from the mycelia of I. geotropa (CgmycLAO). Fractionated aqueous extracts of 15 species of mushrooms show that LAO activity against L-Leu correlates with antibacterial activity. We confirm that the LAO activities mediate the antibacterial actions of ApLAO, CgLAO and CgmycLAO. Their antibacterial activities are greater against Gram-negative versus Gram-positive bacteria, with inhibition of growth rate, prolongation of lag-phase, and decreased endpoint biomass. In Gram-positive bacteria, they mainly prolong the lag phase. These in vitro antibacterial activities of CgLAO and CgmycLAO are confirmed in vivo in tomato plants, while ApLAO has no effect on disease progression in planta. Transmission electron microscopy shows morphological changes of R. solanacearum upon LAO treatments. Finally, broad specificity of the antibacterial activities of these purified LAOs were seen for in vitro screening against 14 phytopathogenic bacteria. Therefore, these fungal LAOs show great potential as new biological phytoprotective agents and show the fruiting bodies of higher fungi to be a valuable source of antimicrobials with unique features.